Inventory Control Analysis Using The EOQ Method At CV Sudut Cantik - Jamil, R. Moh Shaf Hal; Rahmawati, Zulfia; Widuri, Trisnia (Jurnal Ilmu Sosial Mamangan, 2025)
This research aims to determine the inventory control carried out by CV Sudut Cantik. The data used in this research is primary data obtained from interviews and secondary data obtained from company records for one year (January – December 2023). The data analysis method used in this research is Economic Order Quantity (EOQ) method, which aims to find out economical orders, Total Inventory Cost (TIC), Safety Stock (SS), and ReOrder Point (ROP). Using a descriptive quantitative research approach. Data were analyzed using POM-QM For Windows V5.3. The research results obtained are the Total Inventory Cost according to company policy for products  namely Daviena Skincare Glowing Series Package is IDR 337,725, while based on the EOQ method is IDR IDR 34,155.